2022
DOI: 10.1177/00220221211072790
|View full text |Cite
|
Sign up to set email alerts
|

Are Different Two-Dimensional Models of Culture Just a Matter of Different Rotations? Evidence From the Analysis Based on the WVS/EVS

Abstract: There is a need for a simple and graspable model of culture covering the main cultural differences across modern nations. A two-dimensional model might be a reasonable choice. We analyzed data from the World Values Survey and the European Values Study to test whether different two-dimensional models are factor rotations of each other. We took into account criticisms regarding the choice of items in Inglehart’s analysis of the same data source. Nevertheless, we replicated his dimensions. By means of factor rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…A statistical analysis of major published cultural variables revealed that the variables are dominated by two factors that are reflected in most studies of cultural differences, though rotated differently in each study (Fog, 2021). This finding is confirmed by another study based on primary data rather than published variables and factors (Kaasa & Minkov, 2022).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…A statistical analysis of major published cultural variables revealed that the variables are dominated by two factors that are reflected in most studies of cultural differences, though rotated differently in each study (Fog, 2021). This finding is confirmed by another study based on primary data rather than published variables and factors (Kaasa & Minkov, 2022).…”
supporting
confidence: 74%
“…We may ask if there is a right or optimal rotation angle for the factors. Kaasa and Minkov (2022) say that the rotation is arbitrary, but these authors are in fact relying on Minkov’s revised model (Minkov & Kaasa, 2021), which is a two-dimensional model that aligns almost perfectly with the F1 and F2 dimensions of the present study. The rotation is not arbitrary if we are seeking theoretical explanations for the relationship between different cultural variables.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Related to this complexification of IvC are calls for the field to move “beyond” IvC by investigating how this binary intersects with other factors (e.g., Montuori & Purser, 2000; Oyserman et al, 2002; Sztompka, 2014; Turiel, 2004; Zabel, 2015). In that respect, Kaasa and Minkov (2022) argue for the general value and desirability of “two dimensional” models for understanding and differentiating cultures (as opposed to more complex multidimensional arrangements). Thus, taking IvC as one dimension, scholars have explored how it intersects with various other second dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers of culture have not yet reached agreement on what dimensions provide the best description of culture ( Beugelsdijk and Welzel, 2018 ; Minkov, 2018 ; Kaasa and Minkov, 2022 ), no one seems to question that a relatively small number of abstract and directly unobservable factors are the best descriptors of cultural diversity. If the goal is to understand something substantial about the relationship between culture and personality, then it is necessary to concentrate on the underlying dimensions rather than an endless number of small details.…”
Section: Comments On Traits and Culturementioning
confidence: 99%